Do in vitro fertilization, intrauterine insemination or female infertility impact the risk of congenital anomalies in singletons? A longitudinal national French study. Issue 3 (30th December 2020) - Fauque, Patricia; De Mouzon, Jacques; Devaux, Aviva; Epelboin, Sylvie; Gervoise-Boyer, Marie-José; Levy, Rachel; Valentin, Morgane; Viot, Géraldine; Bergère, Marianne; De Vienne, Claire; Jonveaux, Philippe; Pessione, Fabienne
Abstract: STUDY QUESTION: Do IVF, IUI or female infertility (i.e. endometriosis, polycystic ovary syndrome [PCOS] and primary ovarian insufficiency [POI]) lead to an increased risk of congenital anomalies in singletons? SUMMARY ANSWER: After multivariable adjustments, the increased risks of congenital defects associated with IUI were no longer significant, but the underlying maternal infertility presented a potential emental risk, in addition to the risk associated with IVF. WHAT IS KNOWN ALREADY: Most epidemiological studies suggest that singletons born from ART have a higher risk of birth defects, specifically musculoskeletal, cardiovascular and urogenital disorders. However, most of these studies were established on data obtained at birth or in the neonatal period and from relatively small populations or several registries. Moreover, to our knowledge, female infertility, which is a potential confounder, has never been included in the risk assessment. STUDY DESIGN, SIZE, DURATION: Using data from the French National Health System database, we conducted a comparative analysis of all singleton births (deliveries ≥22 weeks of gestation and/or >500 g of birthweight) in France over a 5-year period (2013–2017) resulting from fresh embryo or frozen embryo transfer (fresh-ET or FET from IVF/ICSI cycles), IUI and natural conception (NC). Data were available for this cohort of children at least up to early childhood (2.5 years old). PARTICIPANTS/MATERIALS, SETTING, METHODS: A total of 3 501 495 singleton births were included (3 417 089 from NC, 20 218 from IUI, 45 303 from fresh-ET and 18 885 from FET). Data were extracted from national health databases and used to identify major birth defects. Malformations were classified according to the 10th revision of the International Classification of Disease. To analyse the effect of mode of conception, multivariable analyses were performed with multiple logistic regression models adjusted for maternal age, primiparity, obesity, smoking, history of high blood pressure or diabetes and female infertility. MAIN RESULTS AND THE ROLE OF CHANCE: In our cohort of children, the overall prevalence of congenital malformations was 3.78% after NC, 4.53% after fresh-ET, 4.39% after FET and 3.91% after IUI (132 646 children with major malformations). Compared with infants conceived naturally, children born after fresh-ET and after FET had a significantly higher prevalence of malformations, with an adjusted odds ratio (aOR) of 1.15 [95% CI 1.10–1.20, P < 0.0001] and aOR of 1.13 [95% CI 1.05–1.21, P = 0.001], respectively. Among the 15 relevant subgroups of malformations studied, we observed a significantly increased risk of eight malformations in the fresh-ET group compared with the NC group (i.e. musculoskeletal, cardiac, urinary, digestive, neurological, cleft lip and/or palate and respiratory). In the FET group, this increased risk was observed for digestive and facial malformations. The overall risk of congenital malformations, and the risk by subtype, was similar in the IUI group and the NC group (overall risk: aOR of 1.01 [95% CI 0.94–1.08, P = 0.81]). In addition, there was an overall independent increase in the risk of congenital defects when the mothers were diagnosed with endometriosis (1.16 aOR [95% CI 1.10–1.22], P < 0.0001), PCOS (1.20 aOR [95% CI 1.08–1.34], P = 0.001) or POI (1.52 aOR [95% CI 1.23–1.88], P = 0.0001). Chromosomal, cardiac and neurological anomalies were more common in the three maternal infertility groups. LIMITATIONS, REASONS FOR CAUTION: Male infertility, the in vitro fertilization method (i.e. in vitro fertilization without or with sperm injection: conventional IVF vs ICSI) and embryo stage at transfer could not be taken into account. Furthermore, residual confounding cannot be excluded as well as uncertainties regarding the diagnostic criteria used for the three female infertilities. Findings for specific malformations should be interpreted with caution because the number of cases was small in some sub-groups (potentially due to the Type I error or multiple testing). WIDER IMPLICATIONS OF THE FINDINGS: In this large study, after multivariable maternal adjustments, a moderately increased risk of defects subsisted after IVF, while those associated with IUI were no longer significant. In addition, our results showed that underlying maternal infertility could contribute to the increased risk of defects associated with IVF. These novel findings highlight the importance of taking into account the ART treatment methods and the type of infertility. STUDY FUNDING/COMPETING INTEREST(s): This work was supported by the National Agency of Biomedicine. The authors have no competing interests to disclose. TRIAL REGISTRATION NUMBER: NA.